Managing information and knowledge in Malaysia's flood management: Towards a new framework - Ahmad M.N.; Othman M.; Zakaria N.H.; Mohd Rodzi M.Z. (IOS Press, 2023)
The management of knowledge is crucially influenced by how information is governed, managed and shared. In an emergency situation such as a disaster event, any proposed information and knowledge management solution - whether it be a technological-based solution or non-technological solution - should be based on a clear framework. Such a framework can range from a highlevel conceptual model to a low-level conceptual model that governs the development of any technological solutions. With a focus on flood management in the Malaysian context, this paper attempts to develop a new framework for flood management that is derived from current problems in Malaysia's flood management and places an emphasis on information and knowledge management. Although the framework is still conceptual, it is sufficient to provide the foundation as a metamodel to ensure interoperability, information and knowledge sharing and also to assist the development and integration of IS/IT systems in supporting flood management. The framework also serves as a foundation for future quantitative and qualitative research that might confirm or disprove the patterns identified here. © 2014 The authors and IOS Press. All rights reserved.